Detection of Influenza C Viruses Among Outpatients and Patients Hospitalized for Severe Acute Respiratory Infection, Minnesota, 2013-2016 - Thielen, Beth K; Friedlander, Hannah; Bistodeau, Sarah; Shu, Bo; Lynch, Brian; Martin, Karen; Bye, Erica; Como-Sabetti, Kathryn; Boxrud, David; Strain, Anna K; Chaves, Sandra S; Steffens, Andrea; et al. (Clinical infectious diseases, 2017)
Existing literature suggests that influenza C typically causes mild respiratory tract disease. However, clinical and epidemiological data are limited. Four outpatient clinics and 3 hospitals submitted clinical data and respiratory specimens through a surveillance network for acute respiratory infection (ARI) from May 2013 through December 2016. Specimens were tested using multitarget nucleic acid amplification for 19-22 respiratory pathogens, including influenza C. Influenza C virus was detected among 59 of 10 202 (0.58%) hospitalized severe ARI cases and 11 of 2282 (0.48%) outpatients. Most detections occurred from December to March, 73% during the 2014-2015 season. Influenza C detections occurred among patients of all ages, with rates being similar between inpatients and outpatients. The highest rate of detection occurred among children aged 6-24 months (1.2%). Among hospitalized cases, 7 required intensive care. Medical comorbidities were reported in 58% of hospitalized cases and all who required intensive care. At least 1 other respiratory pathogen was detected in 40 (66%) cases, most commonly rhinovirus/enterovirus (25%) and respiratory syncytial virus (20%). The hemagglutinin-esterase-fusion gene was sequenced in 37 specimens, and both C/Kanagawa and C/Sao Paulo lineages were detected in inpatients and outpatients. We found seasonal circulation of influenza C with year-to-year variability. Detection was most frequent among young children but occurred in all ages. Some cases that were positive for influenza C, particularly those with comorbid conditions, had severe disease, suggesting a need for further study of the role of influenza C virus in the pathogenesis of respiratory disease.